Perbaikan User Interface dan Analisis Perbandingan Hasil pada Website Lazada.co.id dengan menggunakan Usability Testing dan System Usability Scale (SUS) Questionnaire - Veronica Sonya Souissay; Retno Indah Rokhmawati; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the world, technology is developing rapidly towards digital and mobile. The rapid development of information technology gives many positive influences in life. One of them is buying and selling activities that are getting easier through e-commerce. In Indonesia, one of the most well-known and widely used e-commerce sites is Lazada. But in previous research there were several problems experienced by Lazada users related the interface. These problems also impacted to usability level of the Lazada.co.id website. Therefore, the purpose of this research is to improve the Lazada.co.id website from the interface side. Then, this will be tested to the respondent and assessed using a questionnaire. The results will be compared with the results of previous research obtained from the Lazada.co.id website. The method used in this research is the Integrated Design of Interface (IDI) method until the fourth stage by producing prototypes to improve user interface (UI), usability testing, and the System Usability Scale (SUS) questionnaire. Respondents consisted of six people at the initial interview stage and ten people at the usability testing stage, SUS questionnaire, and user experience interviews. The work background of each respondent varies with the age range of 16-65 years who have used e-commerce Lazada. Through the results of this research, recommendations for improvements through the Lazada prototype get better results compared to previous research on the Lazada.co.id website.